Implementing ICARE training model to enhance Indonesian students’ emceeing skills: Its process and impact - Irfan Efendi; Fathur Rokhman; Rustono Rustono; Rahayu Pristiwati (Indonesian Journal of Applied Linguistics, 2023)
Having a good command of public speaking skills has been considered a pivotal modal for students to gain academic achievement and professional success. Practicing to be a master of ceremony can be a means of elevating public speaking skills. However, mastering the emceeing skills is not an easy task since it requires the students’ competencies to make use of linguistic and non-linguistic resources. The purpose of this study is to elucidate the results of the implementation of the ICARE model (Introduction, Connection, Application, Reflection, and Extension) to enhance students’ linguistic- and non-linguistic-related emceeing skills. This research employed a quantitative and qualitative approaches, using an observation sheet, interview protocol, and pre and posttest. The results showed that the training activities focused on establishing a group collaboration and promoted confidence in linguistic and non-linguistic mastery. The observation results revealed that the application of the ICARE model was considered helpful since it could facilitate teaching and learning activities in a more contextual way, with active, creative, and fun characteristics (joyful learning) and obtained a positive response from the students. They could relate it to everyday life. The statistical results of the pre and posttest scores demonstrated the effectiveness of the ICARE model in enhancing the students’ language and non-language-related emceeing skills. The results affirm the importance of mastering linguistic and non-linguistic elements that contribute to increased public speaking skills.